Prevention of the Trend of Rational Choices Among Millennials in Early Marriage in Yogyakarta - Sumarkan, Sumarkan; Syihabuddin, Atok; Dikuraisyin, Basar; bin Abd. Ghani, Amirul Haqeem (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2025)
This research reveals a new trend in the phenomenon of early marriage among the millennial generation. The motives for early marriage have undergone a transformative change, no longer driven by tradition, parental intervention, cultural norms, or religious figures, but rather influenced by knowledge and personal choice as a result of digital applications. The study also describes the preventive measures taken by judicial institutions to prevent early marriage. This research is qualitative in nature, with primary data obtained through interviews and document studies, including interviews with a sample of millennials and two judges from the Yogyakarta Religious Court.. Key findings of this study are, first, the transformation of early marriage trends in Yogyakarta City stems from changes in social and legal norms shaped by digital figures, trends, and framing. The transformation in millennials' thinking when making decisions about early marriage is due to compliance with norms and the most rational choice. They decided to marry early because it provided economic security amid economic hardship. Second, judicial prevention is carried out through the issuance of Standard Operating Procedures (SOPs) in courts for the legislation of early marriage applications through the SIDIKA application, as it aims to protect personal, social, and economic interests, which are part of the public interest (maslahah mulghah) aligned with the dimensions of maqasid shariah.